Food safety knowledge and attitudes: investigating the potential benefits of on-site food safety training for folklorama, a temporary food service event - Mancini, Roberto (Kansas State University, 2012)
Folklorama in Winnipeg, Manitoba, Canada is a 14-day temporary food service event that explores the many different cultural realms of food, food preparation, and entertainment. The ethnic nature and diversity of foods prepared within each pavilion presents a unique problem for food inspectors as each culture prepares food in their own very unique way. In 2010, the Russian pavilion at Folklorama was implicated in a foodborne outbreak of E.coli O157 causing 37 illnesses and 18 hospitalizations. Both the Department of Health and Folklorama Board of Directors realized a need for implementation of a food safety delivery program that would be more effective than a simple 2-hour food safety course delivered via PowerPoint slides. Until 2011, the 2-hour food safety course delivered to event co-ordinators and food operators for Folklorama pavilions was not mandatory. The course is now mandatory in 2011 for all Folklorama pavilions. Five randomly chosen pavilions were trained on-site, in their work environment, focusing on critical control points specific to their menu. A control group (five pavilions) did not receive on-site food safety training. Critical infractions noted on standardized food inspection reports were assessed. Results of the current study suggest no statistically significant difference in food inspection scores between the trained group and control group. Results imply that the 2-hour food safety course delivered via slides was sufficient to pass public health inspections.
Keywords: Folklorama; Hands-on food safety training; Critical control points; Temporary food service event; Food Science (0359)